Investigating Musculoskeletal Disorders Seen Among Porters (Coolie) - Raveena, Raveena; Pratap, Yash (Journal of Neonatal Surgery, 2025)
Background: It is possible to develop inflammatory and degenerative disorders in the soft tissues of the hands, wrists, elbows, shoulders, necks and lower backs as a result of long-term, intense and repetitive employment. Among railway porters, this research hopes to look at the incidence of musculoskeletal disorders (MSDs). Materials & Methods: The Modified Nordica Questionnaire and the Visual Analog Scale were used to create a questionnaire that was used to evaluate the prevalence of musculoskeletal diseases (MSDs) among railway porters. Due to a lack of knowledge among Railway porters, the question form was administered to the porters of the railroads, and the data was then completed back in the form. The information from all 300 participants was compiled and then imported into MS Excel for further research. Results: All of the participants in the study reported feeling a great deal of pain, and the data indicate that lower back discomfort has had a significant influence on the subjects' ability to do their professions since last year. Seventy per cent of individuals who took part in the research experienced neck discomfort, while fifty per cent claimed shoulder pain, sixty per cent indicated upper back pain, forty per cent reported wrist pain, and 76.5 per cent reported knee pain. Discomfort has been measured at 7.76 on the Visual Analog Scale (VAS). Findings from this study show that porters have a greater than predicted prevalence of musculoskeletal issues. Conclusion: We may conclude that porters have a high prevalence of musculoskeletal problems as a result of this research. The portion of the lower back that has the most impact on all of the porters. Additional research on the issue is required, preferably with a focus on age differences in prevalence rates and subject populations, and a larger sample size overall